The Netherlands-Based Study on the Link between Supportive Interventions and Caregivers of Cancer Patients' Psychological Well-Being - Schilder, Wim (International Journal of Psychology, 2023)
Purpose: The purpose of this study was to find out the link between counseling intervention and psychological wellbeing among care givers of cancer patients in Netherlands. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low-cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Results: The results revealed that there exist conceptual and contextual gaps relating to the study on counseling intervention and psychological wellbeing among care givers of cancer patients in Netherlands. Preliminary empirical review reveals that provision of counseling and any social support was essential in enhancing psychological well- being of family care givers of cancer patients. Unique Contribution to Theory, Practice and Policy: Family System Theory may be used in understanding the impact of terminal illness on the family. The results of this research may be instrumental in suggesting areas concerning counseling that are not effectively conducted with an aim of improving the counseling services in addressing the primary caregiver's needs in hospitals.